2020
DOI: 10.2147/ott.s237751
|View full text |Cite
|
Sign up to set email alerts
|

<p>ANGPTL4 Promotes the Proliferation of Papillary Thyroid Cancer via AKT Pathway</p>

Abstract: Although papillary thyroid carcinoma (PTC) is associated with a generally favorable prognosis, about 15% of patients present recurrence and distant metastasis in the next decade leading to death. Angiopoietin-like 4 (ANGPTL4) is secreted to circulation and belongs to the angiopoietin-like proteins. The expression of ANGPTL4 was increased in several solid tumor tissues compared to corresponding paracancerous tissues. ANGPTL4 was identified as pro-tumorigenic protein, including stimulating tumor cell growth, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…ANGPTL4 has been identified as an oncogene in papillary thyroid carcinoma (PTC). Upregulation of ANGPTL4 promotes PTC cell proliferation and reduces PTC cell cycle arrest 36 . Overexpression of PLK1 promotes the proliferation of renal cell carcinoma (RCC) cells and inhibits apoptosis 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANGPTL4 has been identified as an oncogene in papillary thyroid carcinoma (PTC). Upregulation of ANGPTL4 promotes PTC cell proliferation and reduces PTC cell cycle arrest 36 . Overexpression of PLK1 promotes the proliferation of renal cell carcinoma (RCC) cells and inhibits apoptosis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to evaluate tumor immunogenicity and response to ICIs therapy by analyzing cell cycle-related genes 47 . In this study, two genes (ANGPTL4 and PLK1) of the IGSPP that we constructed were involved in the regulation of the tumor cell cycle 36 , 39 . GSEA of the IGSPP subgroups showed that genes in the IGSPP high-risk group were significantly enriched in cell cycle-related pathways (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All these tissues were embedded in paraffin wax. In addition, 10 fine needle aspiration thyroid samples (6 cases of benign and 4 cases of malignancy) were collected for RNA-Seq [ 17 ]. The basic and pathological characteristics of PTC patients were extracted from medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, in vivo experiments indicated its efficacy in regulating mucosal immune responses and fighting bacterial and viral infections. ANGPTL4 and IGFBP1 are secreted into the plasma and are involved in cell energy metabolism (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%